2020
DOI: 10.1155/2020/2716395
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Comorbid Diabetes on Short-Term Postoperative Outcomes in Stage I/II Colon Cancer Patients Undergoing Open Colectomy

Abstract: Purpose. This study aimed at evaluating the impact of comorbid diabetes on short-term postoperative outcomes in patients with stage I/II colon cancer after open colectomy. Methods. The data were extracted from the National Inpatient Sample database (2005-2010). Short-term surgical outcomes included in-hospital mortality, postoperative complications, and hospital length of stay. Results. A total of 49,064 stage I/II colon cancer patients undergoing open surgery were included, with a mean age of 70.35 years. Of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Zylla et al (25) reported that T2DM was associated with higher infection and readmission rates. Other studies also showed that T2DM was associated with increased postoperative complications, for example, anastomotic leakage and hemorrhage (12,25,26). The possible mechanism was as follows: i) Glycolysis is highly dependent on glucose, and a number of tumour cells rely on glycolysis for energy supply while in the state of hyperglycemia, making uncontrolled hyperglycemia beneficial to cancer cell proliferation (27); and ii) chronic inflammatory disease, such as T2DM, may result in malignant tumors (28).…”
Section: Discussionmentioning
confidence: 99%
“…Zylla et al (25) reported that T2DM was associated with higher infection and readmission rates. Other studies also showed that T2DM was associated with increased postoperative complications, for example, anastomotic leakage and hemorrhage (12,25,26). The possible mechanism was as follows: i) Glycolysis is highly dependent on glucose, and a number of tumour cells rely on glycolysis for energy supply while in the state of hyperglycemia, making uncontrolled hyperglycemia beneficial to cancer cell proliferation (27); and ii) chronic inflammatory disease, such as T2DM, may result in malignant tumors (28).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported that T2DM was associated with increased infection and readmission rate ( 23 ). Lee et al ( 24 ) reported T2DM could increase the postoperative complications, postoperative stay, combined with other diseases and the status of hyperglycemia might contribute to the complications. However, in our study, it was found no statistical difference in terms of postoperative stay or complications, which was consistent with previous studies ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, glycemic control is essential for improving outcomes in patients with cancer. The incidence of T2D in the U.S. general population is 10.5% (Centers for Disease Control and Prevention, 2020), yet diabetes (types 1 and 2) have been reported to occur in 21.94% of patients with early-stage (stage I-II) colon cancer (Lee et al, 2020). Importantly, prior to a cancer diagnosis, patients with T2D have a 27% higher risk of developing colon cancer, the fourth most diagnosed cancer in the United States (American Cancer Society, 2021), compared to individuals without T2D (González et al, 2017).…”
Section: Glycemic Variability In Patients With Stage Ii-iii Colon Cancermentioning
confidence: 99%